Tropical grasses used in haylage production: An integrative review - de-AlmeidaDuarte, Ana Beatriz; Dias-Silva, Tairon Pannunzio; Correa-Viana, Wesleyson Cristian; Chaves-Gurgel, Antonio Leandro; deAraújo, Marcos Jácome; Rocha-Bezerra, Leílson; Rodriguesdo-Nascimento, Romilda; Loiola-Edvan, Ricardo; Vinhas-Ítavo, Luis Carlos; Torreão-Marques, Carlo Aldrovandi; Chay-Canul, Alfonso Juventino (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Haylage is a way of preserving forage with good nutritional value, consisting of the partial removal of water from the plant through the wilting technique. Objective: To identify the main tropical grasses used in haylage production, we developed an integrative review. Methods: Through the PVO mnemonic strategy, which consists of population (P): tropical forage grasses, variables (V): haylage production, and outcome (O): qualitative parameters, we raised the following question: “What are the main tropical forage grasses used in haylage production?” Papers were selected from three different databases: SCOPUS (Elsevier), Web of Science, and Science Direct. Results: The search identified 1,049 articles, but only 10 were considered suitable and included for data extraction. Among the grasses used, 50% were of Cynodon spp., 30% of Panicum maximum, 10% of Festuca rubr, 10% of Dactylis glomerata, and 10% of Trisetum flavescens. Conclusion: We conclude that the main forage grasses used in pre-dried silage production belong to the genera Cynodon spp. and Panicum spp., highlighting Tifton-85 grass and Tanzania grass, respectively.